2011
DOI: 10.1186/1744-9081-7-22
|View full text |Cite
|
Sign up to set email alerts
|

Risk and protective genetic variants in suicidal behaviour: association with SLC1A2, SLC1A3, 5-HTR1B &NTRK2 polymorphisms

Abstract: BackgroundSuicidal behaviour is known to aggregate in families. Patients with psychiatric disorders are at higher risk for suicide attempts (SA), however protective and risk genetic variants for suicide appear to be independent of underlying psychiatric disorders. Here we investigate genetic variants in genes important for neurobiological pathways linked to suicidal behaviour and/or associated endophenotypes, for association with SA among patients with co-existing psychiatric illness. Selected gene-gene and ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(46 citation statements)
references
References 45 publications
(51 reference statements)
2
42
0
2
Order By: Relevance
“…The allelic variability in SLC1A2 may be associated with the underlying diathesis for suicidal acts [Murphy et al, 2011]. The GABRG2 polymorphisms are associated with suicidal behavior in schizophrenia with alcohol dependence or abuse [Zai et al, 2014].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The allelic variability in SLC1A2 may be associated with the underlying diathesis for suicidal acts [Murphy et al, 2011]. The GABRG2 polymorphisms are associated with suicidal behavior in schizophrenia with alcohol dependence or abuse [Zai et al, 2014].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported an association of some variants in genes related to glutamate and GABA systems with suicidal behavior [Kertes et al, 2011; Chiesa et al, 2012; Myung et al, 2012] and MDD [Murphy et al, 2011], while other studies found no association [Sokolowski et al, 2013]. Postmortem microarray studies in suicide and/or MDD report differential expression of GABA receptor subunits, glutamate-ammonia ligase (GLUL), or glutamate receptors in prefrontal and/or limbic brain regions [Choudary et al, 2005; Kim et al, 2007; Klempan et al, 2009; Sequeira et al, 2007, 2009; Tripp et al, 2012].…”
Section: Introductionmentioning
confidence: 99%
“…Murphy et al [62] noted a weak association between suicidal behaviour and rs2269272 polymorphism. Turic et al [63] described association between ADHD and rs2269272 polymorphism.…”
Section: Genetics Of Human Eaats; Possible Involvement In Diseasementioning
confidence: 98%
“…Ряд исследований, проведенных на трансгенных мышах, лишен-ных гена рецептора HTR1B, констатирует возможное вовлечение функци-ональных вариантов гена HTR1B в этиологию таких психических рас-стройств, как агрессивность и алкоголизм (Saudo et al, 1994;Brunner et al, 1999). Ряд независимых исследований подтвердил ассоциацию поли-морфных вариантов гена HTR1B с суицидальным поведением (Gaysina et al, 2003;Lappalainen et al, 1998;New et al, 2001), однако имеются рабо-ты, в которых данная ассоциация не выявлена (Wang et al, 2009;Zupanc et al, 2010;Murphy et al, 2011;Wrzosek et al, 2011).…”
Section: роль генов нейромедиаторных систем мозга в суицидальном повеunclassified